2022
DOI: 10.31557/apjcp.2022.23.9.2953
|View full text |Cite
|
Sign up to set email alerts
|

Invasion and Metastasis Suppression by Anti-Neonatal Nav1.5 Antibodies in Breast Cancer

Abstract: Background: Detectable neonatal Nav1.5 (nNav1.5) expression in tumour breast tissue positive for lymph node metastasis and triple-negative subtype serves as a valid tumour-associated antigen to target and prevent breast cancer invasion and metastasis. Therapeutic antibodies against tumour antigens have become the predominant class of new drugs in cancer therapy because of their fewer adverse effects and high specificity. Objective: This study was designed to investigate the therapeutic and anti-metastatic pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Phenytoin inhibited the transient and persistent Na + current in strongly metastatic MDA-MB-231 cells, thus significantly inhibiting the migration and invasion of MDA-MB-231 cells ( Yang et al, 2012 ). A recent report showed that the size and mass of breast tumour tissue were reduced after treatment with Nav1.5 antibody in triple-negative breast cancer cells MDA-MB-231 ( Sharudin et al, 2022 ). Nav1.5 mRNA and protein are highly overexpressed in breast tumours compared with normal tissues and are associated with cancer recurrence, metastasis, and a low survival rate.…”
Section: Introductionmentioning
confidence: 99%
“…Phenytoin inhibited the transient and persistent Na + current in strongly metastatic MDA-MB-231 cells, thus significantly inhibiting the migration and invasion of MDA-MB-231 cells ( Yang et al, 2012 ). A recent report showed that the size and mass of breast tumour tissue were reduced after treatment with Nav1.5 antibody in triple-negative breast cancer cells MDA-MB-231 ( Sharudin et al, 2022 ). Nav1.5 mRNA and protein are highly overexpressed in breast tumours compared with normal tissues and are associated with cancer recurrence, metastasis, and a low survival rate.…”
Section: Introductionmentioning
confidence: 99%